Controlled release and antibacterial activity of corn starch-based films containing nanocellulose and thymol - Nordin, Norhazirah; Othman, Siti Hajar; Kadir Basha, Roseliza; Abdul Rashid, Suraya (Institute of Physics, 2024)
The use of nanomaterials such as cellulose nanofiber (CNF) and antimicrobial compounds such as thymol (Thy), in starch films may improve the functional properties of films as active packaging films. This study quantifies the retention of thymol in corn starch (CS) and CS films containing cellulose nanofibers (CS/CNF) and investigates the migration of thymol from the films into a food simulant. A kinetic study was performed to evaluate the release of thymol from films into fatty acid food simulant (95% v/v ethanol) at 40 °C. The antibacterial activity of films was investigated via liquid culture assay. It was found that the addition of thymol significantly affects the surface morphology and cross-section of the films. CS/Thy and CS/CNF/Thy films retained thymol at 2.88 ± 0.50 and 11.21 ± 0.75 mg per g of CS/Thy and CS/CNF/Thy films, respectively. The release of thymol was affected by the presence of an intercalating network of CNF, which exhibited Fickian diffusion behavior. The release of thymol reached equilibrium within 48 h for CS/Thy, and 72 h for CS/CNF/Thy films. The CS/CNF/Thy film had a greater inhibitory effect than the CS/Thy film against Listeria monocytogenes and Salmonella Typhimurium. These findings demonstrate the potential applications of these films in improving the shelf life of perishable food products.